Assessing lobster and co-predator feeding rates on barrens-forming sea urchins in South East Australia - Day, Jeremy K.; Knott, Nathan A.; Swadling, Daniel S.; Huggett, Megan J.; Gaston, Troy F. (Frontiers in Marine Science, 2024)
Globally, key predators such as lobsters are thought to control urchins. In south-eastern Australia, the role of Sagmariasus verreauxi (eastern rock lobster) as a key predator of the native urchin Centrostephanus rodgersii (long-spined urchin) has been questioned while the sympatric Heliocidaris erythrogramma (short-spined urchin) may be eaten more frequently. To test this, we tethered and filmed 100 urchins (50 C. rodgersii and 50 H. erythrogramma) outside of a lobster den over 25 nights to identify predators and quantify predation rates, time to feeding onset and handling time. Sagmariasus verreauxi exhibited very low predation rates (4%), despite being filmed walking past urchins repeatedly whereas Heterodontus galeatus (crested horn shark) was the main predator (45%). Predation rates by all predators (lobsters and sharks) were influenced primarily by tethering night but not urchin size or species. Predation increased throughout the study and while H. erythrogramma and C. rodgersii were eaten at similar rates, there was a trend for lobsters to eat H. erythrogramma and sharks to eat C. rodgersii. Feeding onset had no significant predictors though large C. rodgersii took longer to handle during feeding for both predators. Importantly, sharks readily consumed 25 C. rodgersii up to 121 mm Test Diameter (TD) while lobsters only ate one C. rodgersii (58 mm TD). These findings, although from only one test location, provide important insights into the species eating urchins and highlight the potential significance of overlooked predators such as H. galeatus.